Community of Care Amid Pandemic Inequality: The Case of Filipino Migrant Domestic Workers in the UK, Italy, and Hong Kong - Vilog, Ron Bridget T. (Animo Repository, 2021)
The study examines the experiences, coping strategies, and responses of Filipino migrant domestic workers (FMDW) to inequalities amid the COVID-19 pandemic. The collected narratives of migrant leaders from Italy, the U.K., and Hong Kong reveal that FMDWs employ their notions, ethics, and practices of care/care work in coping with the structural and social inequalities caused by the pandemic. We argue that the labor of care exhibited by FMDWs goes beyond the dichotomies of paid work and unpaid obligations of social reproduction. A “community of care” is manifested, which fosters community-building and solidarity in response to social exclusion and inequalities brought about by the COVID-19 crisis. The narratives also indicate a dynamic realignment of care circulation, with FMDWs becoming agents of multidirectional care.